The Impact of the COVID-19 Pandemic on Mediation and New Zealand’s Dispute Resolution System - Morris, Grant (Victoria University of Wellington Law Review, 2024)
The COVID-19 pandemic has transformed mediation practice in New Zealand’s institutional, government-led mediation regimes. The introduction of lockdowns, social distancing and personal protective equipment created a "new normal" for the delivery of consensual third-party dispute resolution in this area. Many of the changes introduced during the pandemic remain despite the removal of restrictions in 2022. This article explores New Zealand’s online alternative dispute resolution (ADR) capacity on the eve of the pandemic. This limited capacity was severely tested during the first lockdown in 2020, highlighting barriers and challenges but also opportunities. However, it was the second major lockdown beginning in August 2021 that cemented many of the changes. In addition to exploring the New Zealand experience, this article provides specific case studies, such as employment mediation, and make some comparisons with apposite overseas jurisdictions. ADR, and mediation in particular, is at a crossroads. A choice must now be made whether to return to a primarily in-person model or continue to emphasise online delivery.